C-reactive protein is an independent predictor for 1-year mortality in elderly patients undergoing hip fracture surgery: A retrospective analysis. Issue 43 (October 2016) - Kim, Byung-Gun; Lee, Young-Kyun; Park, Hee-Pyoung; Sohn, Hye-Min; Oh, Ah-Young; Jeon, Young-Tae; Koo, Kyung-Hoi
Abstract : Abstract: Numerous factors are associated with mortality after hip fracture surgery in elderly patients. The aim of this study was to investigate whether preoperative C-reactive protein (CRP) was an independent risk factor for 1-year mortality after hip fracture surgery in the elderly. The electronic medical records of 772 elderly patients (age ≥ 65 years) undergoing hip fracture surgery from May 2003 to November 2011 were reviewed retrospectively. The patients comprised a high CRP group (>10.0 mg/dL) and low CRP group (≤10.0 mg/dL), based upon preoperative CRP levels. The overall 1-year mortality was 14.1%; the value was significantly higher in the high CRP group than in the low CRP group (31.8% vs 12.5%; P  < 0.001). On binary logistic regression, body mass index (odds ratio [OR], 0.93; 95% confidence interval [CI], 0.88–0.99; P = 0.025), history of malignancy (OR, 2.59; 95% CI, 1.47–4.57; P = 0.001), American Society of Anesthesiologists physical status (ASA PS) class 3–4 (OR, 1.96; 95% CI, 1.25–3.07; P = 0.003), preoperative albumin (OR, 0.39; 95% CI, 0.25–0.61; P  < 0.001), preoperative CRP > 10.0 mg/dL (OR, 2.04; 95% CI, 1.09–3.80; P = 0.025), postoperative intensive care unit (ICU) admission (OR, 2.29; 95% CI, 1.15–4.59; P = 0.019), and creatinine on the second postoperative day (OR, 1.20; 95% CI, 1.00–1.45; P = 0.048) were independent predictors of 1-year mortality after hip surgery. Male gender and low preoperative hemoglobin were associated with in-hospital mortality, whereas delayed surgery and femoral neck fracture were related to the 6-month mortality. Low preoperative albumin and low body mass index predicted the 6-month and 1-year mortality. An increased preoperative CRP level, particularly >10.0 mg/dL, was associated with the 1-year mortality after hip fracture surgery in the elderly. In addition, a history of malignancy, high ASA PS score, and postoperative ICU admission were related to mortality after hip fracture.